Gestational diabetes mellitus remains the risk factor for neonatal adverse outcomes in multiparous women - Xiang, Yuxin; Zhang, Siqi; Li, Yang; Dong, Wenbin; Luo, Qingqing; Lei, Xiaoping (Frontiers in Pediatrics, 2025)
PurposeFollowing China's universal two-child policy, the number of multiparous women increased by 90 million, coinciding with a rise in gestational diabetes mellitus (GDM). Previous studies have indicated that GDM can be effectively managed through antenatal care and lifestyle interventions. This study aims to explore whether GDM still remains a risk factor for adverse neonatal outcomes among multiparous women after the implementation of the universal two-child policy and the enhancement of antenatal care in China.MethodA total of 7,496 multiparous women were categorized into four groups: those without any complications, those with GDM only, those with non-GDM complications, and those with both GDM and non-GDM complications. Logistic regression models were employed to calculate the adjusted odds ratio (aOR) and its 95% confidence interval (CI) for each outcome. Stratified analysis (based on maternal age) and sensitivity analysis (restricted to multiparas with GDM and/or hypertensive disorders in pregnancy) were carried out to evaluate the robustness of the results.ResultsCompared to infants born to multiparous women with GDM alone, infants born to multiparas without any complications had lower risks of preterm birth (PTB) (aOR 0.57, 95% CI 0.46–0.70), macrosomia (aOR 0.60, 95% CI 0.43–0.83), large for gestational age (aOR 0.53, 95% CI 0.44–0.61). When considering multiparous women with GDM with non-GDM complications, the offspring had higher risks of PTB (aOR 1.98, 95% CI 1.33–2.96), LBW (aOR 2.49, 95% CI 1.54–4.01), and small for gestational age (aOR 4.82, 95% CI 2.41–9.65).ConclusionDespite advancements in China's prenatal care system following the two-child policy, GDM persists as a modifiable, high-impact risk factor for neonatal adverse outcomes in multiparous women. Crucially, the synergistic effects of GDM with other pregnancy complications amplify these risks, necessitating early screening (e.g., first-trimester glucose profiling), intensified glycemic management protocols, and family-centered interventions tailored to China's unique sociodemographic landscape.